Operationalizing and Evaluating Synchronous Virtual Group Health Interventions: Wide-Scale Implementation at a Tertiary Care Academic Hospital - Neesha Hussain-Shamsy; Ian McMillan; Sheridan Cook; Alyssa Furfaro-Argier; Andrea Sadler; Faith Delos-Reyes; Lori Wasserman; Sacha Bhatia; Danielle Martin; Emily Seto; Simone N Vigod; Juveria Zaheer; et al. (Journal of Medical Internet Research, 2022)
Group-based health interventions are an important component of health promotion and management. To provide continuity of care throughout the COVID-19 pandemic, our institution undertook a rapid pivot to delivering group-based health interventions via a videoconferencing service which was securely embedded into both the electronic medical record and the patient portal to sustainably address immediate health service delivery needs during the pandemic and beyond. In this paper, we (1) describe the institutionally driven operationalization of a system to provide integrated synchronous video group visits across our hospital and (2) present a proposed strategy to comprehensively evaluate outcomes regarding their implementation, quality, and impact. Lessons for other institutions and the potential future role of synchronous video group visits to enhance how care can be scaled for delivery are discussed.